2016
DOI: 10.1002/jctb.4914
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic biodegradation of MTBE in a field site above the Israeli Coastal Aquifer: evidence from δ13C compound‐specific isotope analysis

Abstract: BACKGROUND: The fuel additive, methyl tert-butyl ether (MTBE), is one of the most frequently occurring groundwater pollutants worldwide. The present study focused on assessing microbial degradation of MTBE in groundwater below a gasoline station situated above the Israeli Coastal Aquifer. Groundwater was monitored in six monitoring wells over a time period of 2.5 years. RESULTS: The site water geochemistry indicated that anaerobic conditions prevailed in two of the most contaminated wells. During a year MTBE c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…4). Field studies addressing the aerobic bioattenuation of MTBE in the saturated zone have suggested its inhibition by BTEX compounds due to either preferred utilization of the latter or depletion of electron acceptors and nutrients (Gafni et al, 2016). Indeed, aerobic MTBE degradation by the model bacterium Methylibium petroleiphilum PM1 was inhibited by BTEX (Joshi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…4). Field studies addressing the aerobic bioattenuation of MTBE in the saturated zone have suggested its inhibition by BTEX compounds due to either preferred utilization of the latter or depletion of electron acceptors and nutrients (Gafni et al, 2016). Indeed, aerobic MTBE degradation by the model bacterium Methylibium petroleiphilum PM1 was inhibited by BTEX (Joshi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The studied sites were characterized by different geochemical parameters: anaerobic with a negative redox potential, low nitrate and sulfate concentrations and high concentrations of dissolved manganese and iron as well as aerobic with high concentration of dissolved oxygen and a positive redox potential. In the anaerobic zone, a decrease in MTBE concentrations during a year, was accompanied by a significant change in δ 13 C from −31.4 to −11.8‰ (Gafni et al 2016;Gelman et al 2014). Based on carbon isotopic enrichment factors (E) of −17.2‰, determined in the microcosm experiments under sulfate reducing and methanogenic conditions, a half-life value of~1 year was estimated (Gafni et al 2016).…”
mentioning
confidence: 99%
“…In the anaerobic zone, a decrease in MTBE concentrations during a year, was accompanied by a significant change in δ 13 C from −31.4 to −11.8‰ (Gafni et al 2016;Gelman et al 2014). Based on carbon isotopic enrichment factors (E) of −17.2‰, determined in the microcosm experiments under sulfate reducing and methanogenic conditions, a half-life value of~1 year was estimated (Gafni et al 2016). In another study, where an active remediation by increasing oxygen level in groundwater was applied, significant decrease in MTBE concentrations was accompanied by small shifts in carbon isotope values.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to their results, the use of Streptomyces strains as bioremediation agents seems very promising in terms of clofibric acid degradation. Gafni et al , investigated the in situ biodegradation of gasoline products in groundwater, in which these pollutants undergo processes of natural attenuation including volatilisation, dilution, sorption, and microbial degradation. Finally, the biodegradation of waste products from the poultry industry was the subject of work by Stiborová et al Specifically, they isolated keratin‐degrading bacteria from poultry, in order to study their role in processing keratin waste.…”
mentioning
confidence: 99%